Presence of the past : memory, heritage and childhood in post-war Britain - Krips, Valerie, 1939- (New York ; London : Garland, 2000)
This book studies the interaction of heritage and fiction written for children over a forty year period in Britain. Examples range from new interactive displays in museums to historical re-enactment and the teaching of 'living history'.
Book Cover; Title; Contents; Series Editor's Foreword; Preface; Introduction: Arrears of Memory; Lieux de Memoire; The Trace of Old Characters; Forgetting the Past; The Taint of History; The Memory of Objects; Bibliography; Index.
Includes bibliographical references (pages 117-122) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Children's literature, English -- Great Britain -- History and criticism; English literature -- 20th century -- History and criticism; History in literature; Children's literature, English -- History and criticism; Littérature de jeunesse anglaise -- Histoire et critique; Littérature anglaise -- 20e siècle -- Histoire et critique; Histoire dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Children's literature, English; English literature; History in literature; Great Britain; 1900-1999; History; Criticism, interpretation, etc